Financial Cryptography and Data Security FC 2012 Workshops, USEC and WECSR 2012, Kralendijk, Bonaire, March 2, 2012, Revised Selected Papers - Blyth, Jim.; Dietrich, Sven.; Camp, L. Jean.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the workshop on Usable Security, USEC 2012, and the third Workshop on Ethics in Computer Security Research, WECSR 2012, held in conjunction with the 16th International Conference on Financial Cryptology and Data Security, FC 2012, in Kralendijk, Bonaire. The 13 revised full papers presented were carefully selected from numerous submissions and cover all aspects of data security. The goal of the USEC workshop was to engage on all aspects of human factors and usability in the context of security. The goal of the WECSR workshop was to continue searching for a new path in computer security that is Institutional review boards at academic institutions, as well as compatible with ethical guidelines for societies at government institutions.
Linguistic Properties of Multi-word Passphrases -- Understanding the Weaknesses of Human-Protocol Interaction -- High Stakes: Designing a Privacy Preserving Registry -- Protected Login -- Enabling Users to Self-manage Networks: Collaborative Anomaly Detection in Wireless Personal Area Networks -- A Conundrum of Permissions: Installing Applications on an Android Smartphone -- Methodology for a Field Study of Anti-malware Software -- My Privacy Policy: Exploring End-user Specification of Free-form Location Access Rules -- A Refined Ethical Impact Assessment Tool and a Case Study of Its Application -- Ethics Committees and IRBs: Boon, or Bane, or More Research Needed -- Ethical and Secure Data Sharing across Borders -- Author Index.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Data Encryption; e-Commerce/e-business.; Computers and Society; Information Systems Applications (incl. Internet).